The effect of ketotifen on inflammatory markers in allergic conjunctivitis: an open, uncontrolled study - Martín, Andrea P. (2003)
Background: The efficacy and safety of ketotifen eye drop treatment in allergic conjunctivitis (AC) management is perfectly known by several studies, but the mechanism of action at the biochemical levels is poorly understood so we decided to perform an open, uncontrolled study in order to investigate the effect of the topical administration of ketotifen fumarate 0.05% on biochemical markers of inflammation on conjunctival cells in patients with AC. Methods: Nineteen patients with symptoms and signs of AC (itching, discharge, burning, redness, increase in the watery discharge, swelling and follicles) and with a history of allergy were prescribed with two daily instillation of one drop of eyewash ketotifen fumarate 0,05% in both eyes during thirty days. They were studied by measuring clinical and immunologic parameters. Results: Ketotifen fumarate treatment significantly reduced the total symptoms and signs score for each patient as well as each symptoms and signs at all time points compared with day 0 (p < 0.0001 and p < 0.016, respectively). Although the percentage of HLA-DR+ epithelial cells diminished only in 58% of patients, the numbers of CD29+ and eotaxin+ epithelial cells dropped significantly in 68% and 73% of them (p < 0.0062 and [removed] Indications:19 patients with allergic conjunctivitis with symptoms of itching, tearing, burning, redness and signs of increased watery discharge, swelling, and presence of follicles. Coexisting diseases were hay fever, asthmatic bronchitis and dermatitis. Patients:19 patients, 8 males and 11 females, aged between 6 and 63 years. TypeofStudy:An open, uncontrolled study investigating the effect of Zaditen administration on biochemical markers of inflammation on conjunctival cells in patients with allergic conjunctivitis (AC). DosageDuration:One drop of 0.05% ophthalmic emulsion on both eyes topically (twice daily instillations). Duration: 30 days. One drop of 0.05% eye drops topically bid to both eyes. Duration: 30 days. Results:After 7 days of treatment, 10 (53%) patients showed improvements of their symptoms and signs (p < 0.0001). With continued treatment through day 14, symptoms control was achieved in 14 (76%) patients (p < 0.0001). Moreover, administration of 0.05% Zaditen eye drops for 30 days significantly (p < 0.0001) reduced the TSSS for each patient between days 0 and 30. Treatment with this drug had clinical effects on burning, watery discharge, and swelling, particularly, at the end of the treatment. Every other symptom was significantly reduced (p < 0.016) at any time of clinical evaluation. The effect of the treatment was also studied on the expression of different molecules on CD45 negative cells by fluorescence activated cell sorting (FACS). It is worth to note that cells studied which were obtained by conjunctival scraping never contained more than 3% of CD45+ cells. When the expression of HLA-DR, CD29 and eotaxin on EC was evaluated after the treatment, a drop in the percentage of those positive EC in 58%, 68% and 73% of patients, respectively was found. Although the variation in percentage of HLA-DR+ conjunctival EC was not significant, the percentage of CD29+ and eotaxin + EC significantly decreased (p < 0.0062 and < 0.0082, respectively) at the end of the treatment. In 9/19 patients a simultaneous drop in EC positive for CD29 and eotaxin was observed. No correlation between variations in mean fluorescent intensity and percentage of positive EC for these markers before and after the treatment was found. FreeText:All patients had a history of allergy. Different symptoms (itching, tearing, burning, redness) and signs (watery discharge increase, swelling, presence of follicles) of allergic conjunctivitis were evaluated at their enrollment (day zero) and at different times after starting treatment (7, 15 and 30 days). Symptoms and signs were classified in four stages: 0-Absent; 1-Mild; 2-Moderate and 3-Severe. The total symptoms and signs score (TSSS) for each subject were obtained by adding the values of each symptoms and signs divided by the total number of them. Samples of conjunctival scrapings were collected from both eyes of all patients treated on days 0 and 30 using a disposable plastic scoop. Tests: CD29, HLA-DR antigen, and eotaxin expression in conjunctival epithelial cells (EC). AdverseEffects:No adverse events were mentioned. AuthorsConclusions:Here, we corroborated the effectiveness of ketotifen fumarate in decreasing the symptoms and signs of AC in the majority of patients, but more importantly we showed that this drug even though was not effective in reducing the expression of HLA-DR on EC, it significantly decreased the percentage of CD29+ and eotaxin+ EC.